Qualitative phytochemical analysis, thin-layer chromatographic profiling, and antimicrobial potential of banana cultivars - Khan, A.; Swennen, R.; Panda, S.K.; Schoofs, L.; Luyten, W. (Elsevier, 2025)
Background Banana plants possess numerous medicinal properties due to the presence of various phytochemicals. This study aimed to assess the phytochemical profile of the crude extracts of leaf, pseudostem, and corm parts of selected banana cultivars via standard techniques and thin layer chromatography (TLC) and to evaluate their antimicrobial activities against several food-borne and clinically important human pathogens, including two Gram-positive bacteria, six Gram-negative bacteria, and four yeasts. Results The results demonstrated that the Cachaco (41%), Tereza (38%), Fougamou (30%), Pelipita (28%), Giant Cavendish (26%), and Kluai Teparot (26%) cultivars presented significant antimicrobial activity against pathogens compared with Dole (24%), Namwah Khom (20%), and Mbwazirume (16%) cultivars. Moreover, the leaves (40%) of cultivars extracted in water (61%) and acetone (55%) yielded the most active antimicrobial extracts compared with the pseudostem (33%) and corm (26%) extracts prepared in ethanol (38%) or hexane (28%). Overall, the antimicrobial activities with the lowest 50% inhibitory concentration (IC50) values, especially those with values less than 200 µg/mL for bacteria and 100 µg/mL for yeasts, were reported in the leaves of Cachaco and Giant Cavendish, followed by different parts of Tereza, Pelipita, and other banana cultivars. Phytochemical analysis and TLC profiling confirmed the presence of various groups of phytochemicals in the extracts of the selected banana cultivars. Conclusions This study revealed that the Cachaco, Giant Cavendish, Pelipita, and Tereza cultivars possess significant antimicrobial activity, warranting further bioassay-guided antimicrobial studies for the isolation and identification of bioactive compounds, which could be useful as novel drug candidates with the highest potency.